Vertical distribution characteristics of outdoor particulate matter concentration in high-rise buildings during working days and non-working days - Niu BoWen; Fan Yuesheng; Zhang Xin; Wang Huan; Zhou Peitao (E3S Web of Conferences, 2022)
With the acceleration urbanization in China, it is great significance to understand the distribution characteristics of outdoor particulate matter concentration in high-rise buildings during working days and non-working days. In this paper, a high-rise building of different heights (1, 7, 11, 17, 23, 27) in a university in Xi'an is tested and analyzed. The test times are 8:00, 14:00 and 21:00 respectively. The results showed that the change trend of the particulate matter concentration with the increase of vertical height is the same at all times of the non-working day. While the change trend of particulate matter concentration with the increase of vertical height is basically the same at other times except 8:00 on the working day. In addition, the concentration of particulate matter on working days increased significantly compared to non-working days, with the largest increase at 14:00. On non-working days, PM1.0/PM10 and PM2.5/PM10 both showed a trend of first increasing, then decreasing, and then increasing in different time periods. On weekdays, PM1.0/PM10 and PM2.5/PM10 all showed a trend of falling first and then rising in different time periods. This article provides a reference for the development of high-rise buildings and the effective control of particulate matter concentration in high-rise buildings.